(untitled) (LEARNing Landscapes, 2012)
"These times are riven with anxiety and uncertainty" asserts John O’Donohue.1 "In the hearts of people some natural ease has been broken. . . . Our trust in the future has lost its innocence. We know now that anything can happen. . . . The traditional structures of shelter are shaking, their foundations revealed to be no longer stone but sand. We are suddenly thrown back on ourselves. At first, it sounds completely naïve to suggest that now might be the time to invoke beauty. Yet this is exactly what . . . [we claim]. Why? Because there is nowhere else to turn and we are desperate; furthermore, it is because we have so disastrously neglected the Beautiful that we now find ourselves in such a terrible crisis."2